Kinematic analysis of the flight phase of the Nordic combined and ski jump on a large hill (HS-134 m) during the 2009 Nordic World Ski Championships - Svoboda, Z.; Janura, M.; Cabell, L.; Janurova, E. (Acta of Bioengineering and Biomechanics, 2011)
The purpose of this study was to assess the execution of the flight phase in the Nordic combined (NC) among three groups of competitors, representing different skill levels, and to compare them with three groups of ski jumpers (SJs). Thirty NC and thirty SJ competitors, who performed ski jumps on an HS-134 m jumping hill, were divided into three subgroups based on jump length execution. Two-dimensional (2-D) kinematic data were collected from the lower extremities, trunks, and skis of the competitors. The SJ group had a smaller lower extremity angle ( p < 0.05), which results in the larger center of mass anterior movement ( p < 0.05) in comparison to the NC competitors. The NC competitors achieved jump lengths comparable to those of the SJ competitors by having significantly higher in-run velocities.